DEEP LEARNING APPROACH TO TEACHING MULTIPLICATION CONCEPTS USING COIN MEDIA: CLASSROOM ACTION RESEARCH IN ELEMENTARY SCHOOL - Efendi, Rif'an; Siswanto, Deny Hadi; Saputra, Surya Adi (CV. Denasya Smart Publisher, 2025)
This study is a Classroom Action Research (CAR) aimed at improving the understanding of multiplication concepts among Grade II A students of SD N Koroulon 2 Sleman through a Deep Learning approach assisted by coin-based media. The research was conducted in two cycles using the spiral model developed by Kemmis and McTaggart. In the Cycle I, the learning process focused on using coin games as a concrete medium to build conceptual understanding of multiplication. The results showed that only 68% of students achieved learning mastery. Discrepancies were still observed in the achievement indicators, particularly in converting repeated addition into multiplication sentences. Based on the reflection results, improvements were implemented in the Cycle II through strategies such as paired group work, varied learning activities, and the inclusion of a